STUDI PENANGANAN GENANGAN BANJIR DAN ROB SUNGAI MEDURI-BREMI KOTA PEKALONGAN - Edy Susilo; Hani Purwanti; Satria Pinandita (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
Floods and droughts are a problem in most parts of Indonesia. The cause is suspected to be due to changes in land use from an open green land to land covered by buildings. As a result, water infiltration into the soil decreases, and runoff increases. This condition will be overcome by increasing the infiltration of water into the soil. Various attempts have been made using recharge wells and biopores. However, due to the small capacity of the infiltration equipment, it has not been able to overcome the problem of inundation and flooding. Horizontal Recharge Pipe (HRP) with perforated walls has a very large infiltration. The watersheds of the Meduri and Bremi Rivers, which are located in the western part of Pekalongan, are areas that frequently experience inundation and flooding. The results of the analysis of rain data showed that the planned return periods of 2 years, 5 years, 10 years, 25 years, and 50 years respectively for the Meduri watershed were 106.33 mm, 146.98 mm, 172.05 mm, 200.40 mm, and 219.73 mm. As for the Bremi DAS, it is 104.84 mm, 147.62 mm, 173.11 mm, 200.38 mm, 217.98 mm, 233.47 mm, and 247.93 mm. The design flood is calculated using the Gama-1, ITB-1, ITB-2, and Nakayasu methods. With a flow coefficient of 0.455 for the Meduri watershed and 0.439 for the Bremi watershed, the flood discharge plan for the Gama-1 method with return periods of 2 years, 5 years, 10 years, 25 years, and 50 years respectively for the Meduri River is 34.36 m3/sec, 47.49 m3/s, 55.59 m3/s, 64.75 m3/s, and 71.00 m3/s. While the planned discharge of the Gama-1 method for the Bremi River is 49.97 m3/s, 70.36 m3/s, 82.51 m3/s, 95.51 m3/s, 103.61 m3/s, 111.28 m3/s, and 118.17 m3/s. In the LWL condition, it does not rain, and the capacity of the river is sufficient while in the LWL condition and it rains some of the river sections overflows. There are several options for handling this flood, namely A. Motion weirs, ponds, and parapet normalization; B. Dams, ponds, parapet normalization, pumps, and HRP; C. Normalization, parapet, and HRP. Of the three options, it is recommended to choose option C depending on budget availability with the following considerations: low cost, environmentally friendly, increasing groundwater availability, reducing land subsidence, and preventing seawater intrusion, as well as lower operational costs. Keywords: Flood, horizontal recharge pipe, reduction, pump, land use change